Impact of leisure environmental supply on new urban pathology: a case study of Guangzhou and Zhuhai - Yi Liu (Springer Nature, 2021)
Abstract Traditional studies on urban pathology primarily focused on impacts of social disorganization and urban settings, such as crime, polarization between the rich and the poor, pollution, and deteriorating living conditions, whereas there is insufficient attention paid to urban mental health and wellness. To provide fresh insights into the issue of urban mental health and wellness, this paper defines the psychiatric disorder of urban citizens as ‘new urban pathology’ which primarily results from a highly competitive, stressful, and fast-paced urban life. Based on 40 interviews from citizens in two rapidly urbanizing cities in mainland China, this paper attempts to investigate how the supply of leisure facilities affects new urban pathology. There are three general findings of this research: (1) First, new urban pathology commonly exists and varies with urban communities. However, it is not significantly influenced by the pace of city life. It is found that the worse prospect the living standards, the more significant the negative impacts of the new urban pathology. (2) Sufficient urban leisure facilities do have positive impacts on relieving psychological pressure of urban dwellers. Apart from these, residents also achieve stress relief from surrounding therapeutic landscapes like aesthetic public space, well-designed architecture, etc. (3) The perceived usefulness of leisure environment serves as a key factor to mediate the stress-mitigating effect of leisure supply. When leisure facilities’ functions highly match the needs of residents, leisure environmental supply can be utilized effectively, which helps alleviate the new urban pathology. This research advances the literature of urban health studies by tentatively revealing the interaction between the supply of leisure environmental facilities and urban mental health. It suggests that urban practitioners should optimize the quality of facilities rather than simply increasing the quantity for reducing the daily stress of urban life.